Naturalist Intelligence Among the Other Multiple Intelligences [In Bulgarian] - R. Genkov (Bulgarian Journal of Science and Education Policy, 2007)
The theory of multiple intelligences was presented by Gardner in 1983. The theory was revised later (1999) and among the other intelligences a naturalist intelligence was added. The criteria for distinguishing of the different types of intelligences are considered. While Gardner restricted the analysis of the naturalist intelligence with examples from the living nature only, the present paper considered this problem on wider background including objects and persons of the natural sciences.